Physical characteristics, physiological attributes, and on-field performances of soccer goalkeepers - Ziv, G.; Lidor, R. (International Journal of Sports Physiology and Performance, 2011)
The soccer goalkeeper (GK) is required to perform strenuous actions during practice sessions and actual games. One of the objectives of those professionals who work with GKs is to obtain relevant information on physical characteristics and physiological attributes of GKs, and to use it effectively when planning training programs for them. This article has three purposes: (a) to review a series of studies (n = 23) on physical characteristics, physiological attributes, and on-field performances of soccer GKs; (b) to outline a number of methodological limitations and research concerns associated with these studies; and (c) to suggest several practical recommendations for soccer coaches who work with GKs. Four main findings emerged from our review: (a) professional adult GKs usually are over 180 cm tall and have a body mass of over 77 kg; (b) studies on agility and speed produced mixed results, with some showing similar values between GKs and field players and others showing reduced performance in GKs; (c) GKs usually have higher vertical jump values when compared with players playing the various field positions; (d) GKs cover approximately 5.5 km during a game, mostly by walking and jogging. Four methodological limitations and research concerns associated with the reviewed studies were discussed, among them the lack of a longitudinal approach and the lack of on-field performance studies. Three practical recommendations are made for coaches, one of which is that coaches should adopt a careful approach when selecting testing protocols and devices for the assessment of GKs` physiological attributes.